2019
DOI: 10.3390/cli7080099
|View full text |Cite
|
Sign up to set email alerts
|

Land-Use/Land-Cover Changes and Their Impact on Surface Urban Heat Islands: Case Study of Kandy City, Sri Lanka

Abstract: An urban heat island (UHI) is a phenomenon that shows a higher temperature in urban areas compared to surrounding rural areas due to the impact of impervious surface (IS) density, and other anthropogenic activities including changes of land use/land cover (LULC). The purpose of this research is to examine the spatiotemporal land-use/land-cover changes and their impact on the surface UHI (SUHI) in Kandy City, Sri Lanka, using Landsat data and geospatial techniques. LULC classification was made by using a pixel-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
70
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(78 citation statements)
references
References 44 publications
8
70
0
Order By: Relevance
“…The tourism industry has been reported to be the main driving force of the observed rapid development in the study area, as thousands of local and foreign tourists have been visiting Nuwara Eliya [49]. Previous studies, such as Baguio in the Philippines [14,46], Kandy in Sri Lanka [13,51], Bengaluru in India [64], Bogor in Indonesia [46], and Dalat in Vietnam [46], revealed that green spaces, such as forests, declined due to the urban development pressure in their respective study areas. However, our study revealed that the forest areas were intact throughout the study period, owing to strong government policies on forest preservation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The tourism industry has been reported to be the main driving force of the observed rapid development in the study area, as thousands of local and foreign tourists have been visiting Nuwara Eliya [49]. Previous studies, such as Baguio in the Philippines [14,46], Kandy in Sri Lanka [13,51], Bengaluru in India [64], Bogor in Indonesia [46], and Dalat in Vietnam [46], revealed that green spaces, such as forests, declined due to the urban development pressure in their respective study areas. However, our study revealed that the forest areas were intact throughout the study period, owing to strong government policies on forest preservation.…”
Section: Discussionmentioning
confidence: 99%
“…One of the critical environmental impacts of urbanization that has likely affected the mountain city Nuwara Eliya is the Urban Heat Island (UHI) resulting from variations in LST [13,14]. Still, previous studies related to LST have been focused on the Colombo City [3,4,37] and Kandy [13,51] in Sri Lanka.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, LST images obtained at different times are also affected by atmospheric radiation, solar radiation, wind speed, humidity, etc. The LST data obtained in 2004 and 2017 may not have been stable, which will have a certain effect on the analysis of the spatial pattern distribution characteristics of LST [57]. In this paper, the two LST data were selected at the beginning and end of Beijing's urban master plan (2004-2020), which represented the process of urban development of Beijing cities during a completed master plan period.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we hypothesize that the rapid changes in the urban landscape caused the LST pattern in the study area. Most previous studies related to LST focused on the Colombo City [3,4,36] and Kandy [12] [49] in Sri Lanka. This study examines the changes in the urban landscape and their impact on the spatial changes of LST to introduce proper landscape and urban planning in Nuwara Eliya.…”
Section: Mountain Cities In Asia Have Been Developing Since the Colonmentioning
confidence: 99%